Poster Session: Measuring chromatic contrast sensitivity functions from the fovea to far peripheries - Kitakami, Kotaro; Saito, Suguru; Uchikawa, Keiji (Journal of vision (Charlottesville, Va.), 2025)
Human contrast sensitivity functions (CSF) are often utilized in applications such as foveated rendering and saliency analysis. They require CSFs up to higher eccentricities in the peripheral visual field than previous data. We measured chromatic CSF in the peripheral visual field at eccentricities of up to 49 degrees in the nasal and temporal directions of the left eye. The stimulus consisted of a cosine Gabor patch of 10-degree diameter across all eccentricities. We adjusted the luminance of the stimulus components for each eccentricity so that subjects perceived no achromatic change in the stimulus at any spatial frequency. The contrast thresholds were determined using a two-interval forced-choice procedure with the PSI method. The average background luminance was 31 cd/m2, and its chromaticity was CIE D65. The stimulus duration was 0.5sec with 0.5sec increasing and decreasing temporal slopes. The results in the blue-yellow direction show that the CSF differences in eccentricity are small at low spatial frequencies but become larger at higher spatial frequencies. The blue-yellow CSF exhibited a low-pass characteristic, which is consistent with previous studies. For eccentricities up to 21 degrees, the sensitivity tends to decline gradually below 1 cpd, whereas it does steeply above 1 cpd. For eccentricities greater than 21 degrees, 0.6 cpd was found as the change point instead of 1 cpd.